Integrating Strategic Thinking and Transformational Leadership for NPD Idea Support Process - Kazmi, Syeda Asiya Zenab; Naaranoja, Marja; Kytölä, Juha (Elsevier, 2016)
Contemporary businesses implement tactical approaches to support their corporate interests. Based on such logic, the current study presents an attempt to connect the concept of transformational leadership with strategic thinking capability to formulate a diagnostic approach to harness new product idea generation potential in industrial work teams. The idea behind formulating such a research framework is to offer industrial leaders, a mechanism for connectivity among various aspects of operations linked to leadership, corporate strategy and new product idea generation process, of their teams for corporate harmony and effectiveness. The research survey is conducted on 30 team member's representing new product development (NPD) operations at three selected work locations of a European multinational company (Finland, Norway and the UK). The results of our study identified scientifically, the proposed theoretical connection among three industrial operational areas i.e., transformational leadership, strategy thinking and new product idea generation process.
Keywords: Contemporary businesses; corporate interests; transformational leadership; strategic thinking; diagnostic approach; multinational company; new product development; fi=Tuotantotalous|en=Industrial Management|